Humanism and individualism: Maslow and his critics. - Elaine Pearson; Ronald Podeschi (Adult Education Research Conference, 1997)
Using broad-based literature, this study explores Abraham Maslow's humanistic psychology within the contexts of ideological criticism, 20th century U.S. adult education philosophies, and the theoretical issue of philosophical categories.